Cancer screening intervention among black women in inner-city Atlanta--design of a study. - Sung, J F (1992)
This experimental study attempts to determine if an in-home educational intervention conducted by lay health workers (LHWs) can increase adherence among low-income, inner-city black women to schedules for screening for breast cancer and cervical cancer, as well as increase the women's knowledge and change their attitudes regarding these cancers. This paper is a description of the purposes, hypotheses, design, subject recruitment, intervention, and evaluation of the study conducted by Morehouse School of Medicine. Subjects were recruited from a variety of sources, including patients seen in a community health center, women referred by the National Black Women's Health Project (NBWHP), residents of public and senior citizen housing projects, and persons identified in various community settings. Fewer than half of those asked to participate agreed to do so. The 321 women who were recruited were demographically diverse. Overall, about half of these volunteer subjects self-reported at least one Papanicolaou (Pap) smear and one breast examination within a year before enrollment in the study. There was little variation by source of recruitment in compliance with screening recommendations, except that referrals from NBWHP were more likely (P less than 0.01) to have had a Pap test and breast self-examination, while residents of public housing projects were somewhat less likely to have done so. About 35 percent of participants ages 35 and older had a mammogram within an appropriate interval. Participants were randomly assigned to intervention and control groups. Women in the intervention group were visited in their homes by LHWs on three occasions; the LHWs provided education on cancer and reproductive health.(ABSTRACT TRUNCATED AT 250 WORDS)